2019
DOI: 10.1128/jcm.01462-19
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Tuberculosis Diagnosis Using Reporter Enzyme Fluorescence

Abstract: Tuberculosis is the most frequent cause of death in humans from a single infectious agent. Due to low numbers of bacteria present in sputum during early infection, diagnosis does not usually occur until >3 to 4 months after symptoms develop. We created a new more sensitive diagnostic that can be carried out in 10 min with no processing or technical expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Hence, it has been suggested that unknown β-lactamase present in the clinical samples might be cleaved by the fluorogenic substrate because the hypothetical enzyme could have a similar active site to that of the M. tuberculosis enzyme [47].…”
Section: Detection Of M Tuberculosismentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it has been suggested that unknown β-lactamase present in the clinical samples might be cleaved by the fluorogenic substrate because the hypothetical enzyme could have a similar active site to that of the M. tuberculosis enzyme [47].…”
Section: Detection Of M Tuberculosismentioning
confidence: 99%
“…However, sputum may interfere during the detection of this enzyme, increasing the probability of false-positive results. Hence, it has been suggested that unknown β-lactamase present in the clinical samples might be cleaved by the fluorogenic substrate because the hypothetical enzyme could have a similar active site to that of the M. tuberculosis enzyme [ 47 ].…”
Section: Detection Of M Tuberculosismentioning
confidence: 99%
“…The animals were maintained with commercial diet and water ad libitum. The guinea pigs were divided into two groups of four, one group underwent aerosol infection with Mtb strain CDC1551, grown as described previously [ 41 , 42 ] and washed with saline and suspended at an OD 600 of 0.1 prior to nebulization using a Madison chamber, as described previously [ 41 , 43 ]. The other group was used as a control without any infection procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The CDG-3 probe has high selectivity to BlaC, and is used to measure the levels of enzymes and M. tuberculosis in sputum. The sensitivity and specificity for CDG-3 according to the ROC curve were 88.1 and 86.1% in 160 clinical specimens from potential TB patients, with a negative predictive value of 93%; thus, it could be used to predict potential TB patients ( Sule et al, 2019 ). BlaC is secreted by the Tat secretion system in live M. tuberculosis ( McDonough et al, 2005 ); thus, the BlaC-specific reporter enzyme fluorescence test is suitable for the evaluation of the treatment results and phenotypic drug susceptibility.…”
Section: New Promising Diagnostic Techniquesmentioning
confidence: 99%